Poly(butylene cyclohexanedicarboxylate/diglycolate) random copolymers reinforced with SWCNTs for multifunctional conductive biopolymer composites - E. Fortunati; M. Gigli; F. Luzi; N. Lotti; A. Munari; M. Gazzano; I. Armentano; J. M. Kenny (eXPRESS Polymer Letters, 2016)
The objective of this work was to develop a versatile strategy for preparing multifunctional composite films with tunable properties. Novel conductive composites based on the combination of single walled carbon nanotubes (SWCNTs) and biodegradable poly(butylene cyclohexanedicarboxylate/diglycolate) random copolymers (P(BCEmBDGn)) are here presented. In particular, synthesized PBCE homopolymer and two copolymers containing different amounts of ether–oxygen containing co-units, P(BCE90BDG10) and P(BCE70BDG30), have been considered as matrices of SWCNTs based composites. The effect of incorporation of different amounts of SWCNTs (0.1–0.5–0.75–1 wt%) on morphological, thermal, mechanical and electrical properties was deeply investigated. The morphology of the fracture surfaces is affected by the SWCNT presence, while the increase in the SWCNT content does not provide significant microstructure modifications. The thermal properties underlined that nanotubes can act as nucleating agents, favouring the polymer crystallization process. The mechanical behavior demonstrated that the introduction of carbon nanotubes both in the case of PBCE homopolymer and in random copolymers based formulations exerted a reinforcing effect. All composites exhibit high electrical conductivity in comparison to the neat polymers. This work demonstrates that this combinatorial approach can be used to develop materials with tunable and advanced functional properties.